Reliability and repeatability of a smartphone-based 6-min walk test as a patient-centred outcome measure. Issue 1 (9th February 2021) - Mak, Jonathan; Rens, Neil; Savage, Dasha; Nielsen-Bowles, Helle; Triggs, Doran; Talgo, Julia; Gandhi, Neil; Gutierrez, Sebastian; Gutierrez, Santiago; Aalami, Oliver
Abstract: Aims : The 6-min-walk test (6MWT) is a validated proxy for frailty and a predictor of clinical outcomes, yet is not widely used due to implementation challenges. This comparative effectiveness study assesses the reliability and repeatability of a home-based 6MWT compared to in-clinic 6MWTs in patients with cardiovascular disease. Methods and results : One hundred and ten (110) patients scheduled for cardiac or vascular surgery were enrolled during a study period from June 2018 to December 2019 at the Palo Alto VA Hospital. Subjects were provided with an Apple iPhone 7 and Apple Watch Series 3 loaded with the VascTrac research study application and performed a supervised in-clinic 6MWT during enrolment, at 2 weeks, 1, 3, and 6 months post-operatively. Subjects also received notifications to perform at-home smartphone-based 6MWTs once a week for a duration of 6 months. Test–retest reliability of in-clinic measurements and at-home measurements was assessed with an industry standard Cronbach's alpha reliability test. Test–retest reliability for in-clinic ground truth 6MWT steps vs. in-clinic iPhone 6MWT steps was 0·99, showing high reliability between the two tested measurements. When comparing for in-clinic ground truth 6MWT steps vs. neighbouring at-home iPhone 6MWT steps, reliability was 0·74. Conclusion : Running the test–reliability test on both measurements shows that an iPhone 6MWT test is reliable compared to an in-clinic ground truth measurement in patients with cardiovascular disease.